Hyperpolarised NMR to follow water proton transport through membrane channels via exchange with biomolecules. (10th July 2018) - Nastasa, Viorel; Stavarache, Cristina; Hanganu, Anamaria; Coroaba, Adina; Nicolescu, Alina; Deleanu, Calin; Sadet, Aude; Vasos, Paul R.
Abstract : Using hyperpolarised NMR attains sufficient sensitivity to detect water proton uptake in biomolecules following the crossing of membrane channels. Abstract : Water uptake in vesicles and the subsequent exchange between water protons and amide –NH protons in amino acids can be followed by a new, highly sensitive, type of magnetic resonance spectroscopy: dynamic nuclear polarisation (DNP)-enhanced NMR in the liquid state. Water hydrogen atoms are detected prior to and after their transfer to molecular sites in peptides and proteins featuring highly-accessible proton-exchangeable groups, as is the case for the –NH groups of intrinsically disordered proteins. The detected rates for amide proton–water proton exchange can be modulated by membrane-crossing rates, when a membrane channel is interposed. We hyperpolarised water proton spins via dynamic nuclear polarisation followed by sample dissolution (d-DNP) and transferred the created polarisation to –NH groups with high solvent accessibility in an intrinsically disordered protein domain. This domain is the membrane anchor of c-Src kinase, whose activity controls cell proliferation. The hindrance of effective water proton transfer rate constants observed in free solvent when a membrane-crossing step is involved is discussed. This study aims to assess the feasibility of recently-introduced hyperpolarised (DNP-enhanced) NMR to assess water membrane crossing dynamics.